Antibiotic Resistance and Expression Of Resistance-Nodulation-Division Pump- and Outer Membrane Porin-Encoding Genes in Acinetobacter Species Isolated from Canadian Hospitals. Issue 1 (2013) - Fernando, Dinesh; Zhanel, George; Kumar, Ayush
Abstract : BACKGROUND: Bacterial pathogens belonging to the genus Acinetobacter cause serious infections in immunocompromised individuals that are very difficult to treat due to their extremely high resistance to many antibiotics. OBJECTIVE: To investigate the role of resistance-nodulation-division (RND) pumps and porins in the antibiotic resistance of Acinetobacter species collected from Canadian hospitals. METHODS: Clinical isolates of Acinetobacter species collected from Canadian hospitals were analyzed for the expression of genes encoding RND pumps ( adeB, adeG, adeJ, AciBau_2746 and A ciBau_2436 ) and outer membrane porins ( carO, 33 kDa porin and oprD ) using quantitative reverse transcription (qRT) polymerase chain reaction. Species identification of the isolates was performed using a multiplex polymerase chain reaction method for gyrB . RESULTS: The expression of RND pump-encoding genes was widespread in the clinical isolates of Acinetobacter species, with each of the isolates expressing at least one RND pump. adeG was found to be overexpressed in all of the isolates, while adeB was found to be overexpressed in only two isolates. Among the porin-encoding genes, the expression of carO was considerably downregulated among the majority of isolates. CONCLUSION: The present study was the first to analyze the expression of RND pump- and porin-encoding genes in the clinical isolates of Acinetobacter species from Canadian hospitals. The overexpression of genes encoding RND pumps and the downregulation of genes encoding porins was common in clinical isolates of Acinetobacter species from Canadian hospitals, with the AdeFGH pump being the most commonly expressed RND pump.